2018
DOI: 10.3892/br.2018.1160
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modulation during hippocampal development (Review)

Abstract: The hippocampus is located in the limbic system and is vital in learning ability, memory formation and emotion regulation, and is associated with depression, epilepsy and mental retardation in an abnormal developmental situation. Several factors have been found to modulate the development of the hippocampus, and epigenetic modification have a crucial effect in this progress. The present review summarizes the epigenetic modifications, including DNA methylation, histone acetylation, and non-coding RNAs, regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 119 publications
(170 reference statements)
0
8
0
Order By: Relevance
“…Ultimately these changes are associated with differences in hippocampal function in adults sex-dependent manner, and these changes are associated with increased anxiety-like behavior and poorer performance in memory tasks in males [115,116]. Although much is known about changes in DNA methylation and histone modifications in the hippocampus throughout development [117], few studies address epigenetic modifications in this region of the brain in relation to sex or steroid hormone signaling. Tsai and colleagues [118] found a sex difference in histone acetylation in hippocampal tissue of neonatal mice which disappears when pups are treated gestationally with testosterone.…”
Section: Epigenetic Changesmentioning
confidence: 99%
“…Ultimately these changes are associated with differences in hippocampal function in adults sex-dependent manner, and these changes are associated with increased anxiety-like behavior and poorer performance in memory tasks in males [115,116]. Although much is known about changes in DNA methylation and histone modifications in the hippocampus throughout development [117], few studies address epigenetic modifications in this region of the brain in relation to sex or steroid hormone signaling. Tsai and colleagues [118] found a sex difference in histone acetylation in hippocampal tissue of neonatal mice which disappears when pups are treated gestationally with testosterone.…”
Section: Epigenetic Changesmentioning
confidence: 99%
“…Long non-coding RNA (lncRNAs) are another type of non-coding RNA, and it was found that in lnc-RNA-Evf2-knockout mice, the number of interneurons was significantly reduced [ 113 ]. Evf2 recruits distal-less homeobox (DLX) and MeCP2 transcription factors, which are crucial for DNA regulation and expression, ultimately regulating the formation of hippocampal GABAergic interneurons [ 14 ]. In addition, the lack of lnc-RNA-Evf2 appeared to induce epilepsy [ 14 ], which indicates a lack of GABAergic interneurons or dysfunction allowing for runaway excitation [ 114 ].…”
Section: Epigenetic Regulation Of Hippocampal Interneuronsmentioning
confidence: 99%
“…The production of reactive oxygen species (ROS), pro-inflammatory cytokines and chemokines, pro-apoptotic proteins, autophagosome markers, excitatory neurotransmitters and neurotrophic factors may be involved in hippocampal neuropathy and cognitive impairment [ 6 , 7 ]. Recent studies have suggested that epigenetic mechanisms are involved not only in normal hippocampal development and regulation [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], but also in radiation-induced hippocampal pathophysiological changes leading to the development of neurological and neuropsychological disorders [ 15 ]. In this paper, we briefly introduce major mechanisms of epigenetic regulation, followed by a review of the epigenetic regulation of hippocampal neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic changes, such as histone modifications and DNA methylation, have an important role as they provide long‐term changes in cells after mitosis . Today, it is also known that histone modifications and DNA methylation affect synapse formation in the hippocampus .…”
Section: Introductionmentioning
confidence: 99%